Soil erodibility (k) in section of the middle course of the River Basin of the River Poti, Piauí (Brazil) - Santos, Walkyane Alyne Oliveira; Santos, Francílio de Amorim dos; Assunção, Josenete Cardoso; Aquino, Cláudia Maria Sabóia de (Revista Hipótese, 2022)
This study aimed to: e) identify the soil associations in the stretch of the middle course of the river Basin Poti; ii) estimating, by means of the method proposed Crepani et al. (2001), the erodibility of soil associations (K) in that stretch.
Keywords: Hydride feature; Indirect Method; Geoprocessing; Fragility Pedologic